AN ANALYSIS OF THE STUDENTS DIFFICULTIES FACED BY NON-ENGLISH FOREIGN LANGUAGE IN SPEAKING ENGLISH (A Case Study on Third Semester at Teacher Training and Education of Almuslim University in Academic Year 2019/2020 ) - HAJRIANI APRILLIA; ZURAINI ZURAINI (Journal of English Education and Social Science, 2021)
The title of this research is “ An analysis of The Students’ difficulties faced by Non-English Foreign Language in Speaking English (A Case Study On Third Semester At Teacher Training And Education Of Almuslim University In Academic Year 2019/2020 ). The problems of the research are: first, What are the difficulties faced by the third semester students of PGSD Department at Almuslim University in speaking English? Second, What are the factors that make students difficult in speaking English? The purpose of the research is: First, To find out the difficulties faced by the third semester students of PGSD Department at Almuslim University in speaking English. Second, to find out the factors that make students difficult in speaking English. Speaking is used to communicate, convey information, make relationship among people in the world, and etc., because it is one of the abilities to carry out conversation. The student’s problems such as; first, the students less confident to speak English and being afraid to making mistake because they have to think the language of English, so difficult to learn. Second, the students had difficult in using a good grammar to speak in English. Third, the students do not master in vocabulary. And the last, students were difficult in pronunciation because they have to think how to pronounce some word well. Case study is an ideal methodology when a holistic, in depth investigation is needed. Case study had been used in varied investigations, particularly in sociological studies, but increasingly in instruction. The instruments used to collect the data are speaking test and questionnaires. Based on the analysis of the students’ speaking test, the researcher explained that the average percentage of the speaking test is 36.8% the percentage showed that the students faced the problems in Speaking English was from some aspects. The aspects were from: grammar, pronunciation, verb, fluency and compression. Based on the analysis of the students’ questionnaires, the researcher explained that the average percentage of the questionnaire is 1.46 % the percentage showed that the students faced the problems in Speaking English. The sample of this research are the third semester of PGSD’s Students. The average percentage of speaking test based on the total percentage of the students divided into the total students